Performance Assessment of a Lateral Flow Rapid Test (SsRapidVR) Compared with Two Commercial ELISAs in Detecting Strongyloides Infection - Nor Suhada, Anuar; Anizah, Rahumatullah; Norashikin, Samsudin; Zeehaida, Mohamed; Emelia, Osman; Nik Zairi, Zakaria; Hussain, Ahmad; Rahmah, Noordin (The American Society of Tropical Medicine and Hygiene, 2023)
Approximately 600 million people worldwide are infected with Strongyloides stercoralis. Many diagnostic laboratories use serology to detect the infection. SsRapidVR is a prototype IgG4 lateral flow test based on NIE recombinant protein. We compared SsRapid with two commercial IgG-ELISAs (Bordier and Euroimmun) using five sera groups (G1–5, N 5 170). Healthy individuals from nonendemic areas (G1, N 5 33) and Strongyloides larvae-positive patients (G2, N 5 20) showed no significant difference (P . 0.05) among the three assays. The group of other parasitic infections (G3) showed that SsRapid results were more concordant with Bordier ELISA (73%, 35/48) than Euroimmun ELISA (65%, 31/48). In corticosteroid-treated cancer patients who were polymerase chain reaction–positive for Strongyloides (G4, N 5 25), SsRapid showed a higher detection rate (28%, 7/25) than both ELISAs (4%, 1/25). Meanwhile, SsRapid showed significantly less infection prevalence among the endemic area population (G5) than the ELISAs. Overall, SsRapid showed good performance in detecting Strongyloides infection compared with the commercial IgG-ELISAs.